DAMPAK INVESTASI SWASTA YANG TERCATAT DI SEKTOR PERTANIAN TERHADAP PEREKONOMIAN JAWA TENGAH (ANALISIS INPUT-OUTPUT) - SBM, Nugroho; A’fif, Muhammad Faris (Diponegoro Journal of Economics, 2013)
The aims of this research are (1) to analyze how agricultural sector shapes the structure of economy;(2) what the forward and backward linkages of agricultural sector are;(3) how investments affect the construction of the output, household income, and the creation of employment opportunities in the province of Central Java, Indonesia.This research uses Input - Output Table of Central Java in 2008 of local transaction over producer price index with 88 x 88 sectors which then aggregated into 13 x 13 sectors. Analysis on the investments in agricultural sector shows that investments create positive impacts towards the construction of output, construction of income, and, most of all, the creation of jobs in the province of Central Java, Indonesia.